Grado de aprendizaje en conocimientos, procedimientos y actitudes en materia de Sexualidad Infantil - López Novoa, Ibis Llzeth (2001)
The present investigation descriptive correlacional was carried out with the children and girls of the Center Educational Initial "Ana Sofía Guillena Nº Claws 288" of the county of Rioja region of San Martin. The problem, hypothesis, general objective has been structured by means of the relationship of the variable learning in knowledge, procedures and inherent attitudes to the infantile sexuality. The theoretical sustentation of the relationship of the learning in knowledge, procedure~ and attitudes as regards infantile sexuality coming from the home and of the Center Educational Initial, it has been based on the theory of the process of the knowledge, in the psychoanalytical theory of Freud and in the theories psicopedagógicas of the motivation actitudinal. The fom1ation of the alternating central hypothesis, he/ she has had as a positive or negative relationship, while in opposition the null hypothesis denied the relationship. The alternating hypothesis has been derived in three alternating operational hypothesis that correlated to the learning in knowledge and procedures, knowledge and attitudes, procedures and attitudes. Twenty-two educandos conformed the sample. It was used the correlation design and the statistical parameter of correlation by ranges of Spearman, the procedure consisted on the application of the Test: Learning in knowledge, procedures and attitudes as regards infantile sexuality coming from the home and of the Center Educational Initial "Ana Sofía Guillena Nº Claws 288. Madc the test of the hypothesis, their reflective significatividad in the results evidences of a half negative correlation (-1,458) due to the process desvirtuación of teaching to learn knowledge, to the desvirtuación motivacional of attitudes that I eat consequence it determines dcformed procederes. Therefore, the conclusions configure their generality specifying that if you desvirtúa the process of teaching to learn, as well as the motivation actitudinal, these determined deformed procederes as regards infantile sexuality, then the correlation among .the studied variables will have a tendency to be more negative than positive.